Jigar serrozi kasalligiga xos bo’lgan belgilar (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Cirrhosis of the liver is a chronic liver disease and is a severe complication of chronic hepatitis. Morphologically, it is observed that the liver does not swell and its function is severely impaired, and the liver cells - hepatocytes die. Cirrhosis of the liver is the leading cause of death among diseases of the digestive system